2023
DOI: 10.1136/bmj-2022-074425
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and symptom trajectories up to two years after SARS-CoV-2 infection: population based, longitudinal cohort study

Abstract: Objective To evaluate longer term symptoms and health outcomes associated with post-covid-19 condition within a cohort of individuals with a SARS-CoV-2 infection. Design Population based, longitudinal cohort. Setting General population of canton of Zurich, Switzerland. Participants 1106 adults with a confirmed SARS-CoV-2 infection who were not vaccinated before i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 53 publications
3
28
0
1
Order By: Relevance
“…However, for the majority of the sample, regardless of hospitalisation history, various self-Table 6. Descriptive statistics (non-COVID group presented in Table 5) and results of the repeated-measures Group Hospitalisation reported long-COVID symptoms were still present at T2, with sizeable associations between long-COVID symptom load and cognitive function, in line with previous findings [34,35]. Mental health and sleep were still impacted at T2 in COVID-19 survivors, irrespective of hospitalisation history, though depression was lower at T2 than T1 in those without COVID-19-related hospitalisation.…”
Section: Discussionsupporting
confidence: 86%
“…However, for the majority of the sample, regardless of hospitalisation history, various self-Table 6. Descriptive statistics (non-COVID group presented in Table 5) and results of the repeated-measures Group Hospitalisation reported long-COVID symptoms were still present at T2, with sizeable associations between long-COVID symptom load and cognitive function, in line with previous findings [34,35]. Mental health and sleep were still impacted at T2 in COVID-19 survivors, irrespective of hospitalisation history, though depression was lower at T2 than T1 in those without COVID-19-related hospitalisation.…”
Section: Discussionsupporting
confidence: 86%
“…This may mean that any over-representation of long COVID participants in the cohort was exaggerated over time. The lack of a reduction in QALMs lost due to long COVID over time may be attributable to this over-representation, or could have been that the data collection period was too short: for patients suffering long-term symptoms, 3 months is a relatively short period where recovery would be unexpected (Ballouz et al, 2023). Conversely, due to the symptoms of long COVID, loss to follow-up may have been due to fatigue, driven by severe long COVID symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…These limitations create uncertainty regarding the temporal limits of long COVID 12 . For example, a study enrolling unvaccinated individuals who contracted the original strain of SARS-CoV-2 showed that 6 months following acute COVID-19, 22.9% of cases still had long COVID symptoms, but the proportion with symptoms decreased to 18.5% at 1 year and 17.2% after 2 years 13 …”
Section: Medical Aspectsmentioning
confidence: 99%